Fragments for a medieval theory of prosthesis. Issue 7 (9th November 2016) - Walter, Katie L.
Abstract : Medieval surgery adumbrates a theory of the body in which flesh, because it is sanguine, is radically different from the other simple members that make up the body, such as skin, which are understood instead to be spermatic. In contrast with spermatic members, sanguine flesh is renewable, and so is held to be able to stand in the place of lost, diseased or injured spermatic parts. Surgical theory and practice utilises and artificially enhances this natural capacity of flesh to supplement and substitute in its remedies to repair the body, in what is broadly termed 'incarnatyf' medicine in Middle English. This essay suggests that this 'incarnatyf' tradition is part of a missing history of prosthesis, which in turn grounds forms of medieval prosthetic thought in two Middle English examples: the miracle of Cosmas and Damian, in which a living man's rotten leg is replaced with the healthy leg of a dead man; and a series of connected revelations in Bridget of Sweden's Liber Celestis, in which incorporation into the body of Christ is effected through Christ's own practice of surgical prosthesis. Raising questions about the relationship between self and other, life and death, and the human and divine, the medieval 'incarnatyf' imaginary also asks questions about the possibilities and limits of prosthesis as a metaphor for community and for the body of Christ itself.